Spatial changes in the northern Corniche in Jeddah between 1990 and 2019 and its role in attracting tourism - Alharbi, Ebtihal Omar; Alsulami, Morshid Maeyud (Journal of natural sciences, life and applied sciences, 2022)
This study dealt with the spatial changes in the northern Corniche in Jeddah between 1990 and 2019 and their role in attracting tourism. The researcher relied on the quantitative analytical method that the study used to derive the uses of the earth from satellite visuals for three phases for the period between 1990 and 2019. And studying the changes of each use in each stage. Contemporary applied approach is remote sensing and geographic information systems One of the effective tools in the process of knowing spatial changes, and the researcher relied on the applications of GIS and remote sensing in the study phase. The study showed that the length of the coast line in 1990 was about 19.49 km, It reached about 17.06 km in 2004, Thus, the length of the coast line decreased during this period by 2.43 km. The length of the coast line was about 19.78 km in 2019, Thus, the length of the coast line increased during this period by 2.73 km, eats most of the coastal area's waterfronts; The result of drilling and backfilling operations, where between 1990-2004 excavation amounted to 6.5%, and backfilling reached 93.39%. Unchanged areas 0.12%. Between 2004 - 2019 excavation amounted to 13.51%, and backfilling reached 86.1%. Unchanged areas 0.39%. The results showed that urban areas, vegetation cover and roads doubled While the land space, deep water and shallow water decreased during the period from 1990 to 2019. The study recommended setting special laws for the study area to preserve them It should be treated as a recreational and recreational area that receives many visitors and tourists.
Keywords: spatial changes; the northern corniche; attracting tourism